2016
DOI: 10.1097/md.0000000000005634
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response syndrome is more associated with bacteremia in elderly patients with suspected sepsis in emergency departments

Abstract: Early diagnosis of bacteremia for patients with suspected sepsis is 1 way to improve prognosis of sepsis. Systemic inflammatory response syndrome (SIRS) has long been utilized as a screening tool to detect bacteremia by front-line healthcare providers. The value of SIRS to predict bacteremia in elderly patients (≥65 years) with suspected sepsis has not yet been examined in emergency departments (EDs).We aimed to evaluate the performance of SIRS components in predicting bacteremia among elderly patients in EDs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
(35 reference statements)
2
21
0
Order By: Relevance
“…In our study we did not find any association of age and comorbidities with positive blood culture, as noted in some reports [16].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In our study we did not find any association of age and comorbidities with positive blood culture, as noted in some reports [16].…”
Section: Discussionsupporting
confidence: 65%
“…Systemic inflammatory response syndrome (SIRS) is a combination of physiological reactions to various nonspecific, infectious or noninfectious insults. For many years SIRS was a basis for understanding and defining sepsis and some studies find it predictive of bacteremia [15,16]. The main finding of this study is that SIRS number, namely the four SIRS criteria in septic patients are predictive of bacteremia.…”
Section: Discussionmentioning
confidence: 69%
“…Elderly patients clearly show elevated sepsis-induced systemic inflammatory responses 3032. Experiments have also shown that the proinflammatory molecules TNF-α and IL-6 and the anti-inflammatory molecule IL-10 are significantly increased in aged animals compared with young animals 3335.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the gold standard to diagnose GNB infection is based on bacterial culture, which may take hours or days before the result is known and can lead to delayed treatment decisions. The in ammatory mediators induced by GNB infection may result in a signi cant in ammatory response, including fever, tachycardia, and shortness of breath [10]. However, none of the scoring tools, such as qSOFA score and SIRS criteria, had ever been used to predict GNB infection.…”
Section: Introductionmentioning
confidence: 99%